Estrategias pedagógicas interactivas y su impacto en el rendimiento académico de los estudiantes de la unidad educativa Aurora Estrada y Ayala del cantón Babahoyo, Provincia los ríos. - Quevedo Mora, Jazmín Estefanía (2016)
This final report presents the experiences and findings of the research on the subject of interactive didactic strategies in the students of the "Aurora Estrada and Ayala" Educational Unit, Canton Babahoyo, Los Province with a Didactic Guide as a proposal or alternative. For this purpose, the type and design of the research was carefully selected, allowing the collection of valuable information related to the subject and establishing the conclusions as a starting point for selecting a proposal for improvement. In this way the methodology and appropriate techniques were selected. On this information we proceeded to select the interactive pedagogical strategies that are applicable to the classroom work to structure the guide. The intentionality of the design of the didactic guide is to facilitate the work of the teachers and to find also the methodology and strategies that improve the quality of learning and motivate the participation of the children of the institution. The report also includes the bibliographical references consulted and the corresponding annexes.